EFFECT OF FEEDING ODOT GRASS (PENNISETUM PURPUREUM CV. MOTT) SILAGE WITH RICE STRAW AS ABSORBENT ON FEEDING BEHAVIOR OF KACANG GOATS (Pengaruh Pemberian Silase Rumput Odot (Pennisetum Purpureum cv. Mott) dengan Jerami Padi Sebagai Absorban Terhadap.....) - Atamau, Novendi; Jelantik, I Gusti Ngurah; Benu, Imanuel (Universitas Nusa Cendana, 2025)
The aim of this experiment was to determine the effect of feeding odot grass silage (Pennisetum Purpureum cv. Mott) with different levels of rice straw as absorbant on feeding behavior of Kacang goats. Four kacang goats, ranging from 1-1.5 year old with initial body weight of 20.2 kg-22.9 kg, were used in this study using Latin Square Design (RBSL) 4 x 4 with 4 treatments and 4 periods as replications. The treatments were JP0: 100% odot grass silage, JP10: 90% odot grass and 10% rice straw silage, JP20: 80% odot grass and 20% rice straw silage and JP30: 70% odot grass and 30% rice straw silage. The measured variables included the frequency and eating time, frequency and ruminating time, and frequency and resting time. The data obtained were analyzed using Analysis of Variance (ANOVA). The results showed that treatment had no significant effect (P>0,05) on the measured variables. The duration and frequency of feeding ranged from 4.34 to 5.42 hours and 16.50 to 19.87 times per day, duration and frequency of rumination ranged from 11.39 to 14.25 hours and 39.62 hours to 41.87 times per day, and the length and frequency of rest ranged from 5.43 to 7.56 hours, and 30.62 to 32.50 times per day. In conclusion, feeding odot grass silage with different levels of rice straw as an absorbant did not affect the feeding behavior of kacang goats.